1998
DOI: 10.1021/bi972987w
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Analyses of Mutations in the Glycine-Rich Loop of cAMP-Dependent Protein Kinase

Abstract: The conserved glycines in the glycine-rich loop (Leu-Gly 50 -Thr-Gly 52 -Ser-Phe-Gly 55 -ArgVal) of the catalytic (C) subunit of cAMP-dependent protein kinase were each mutated to Ser (G50S, G52S, and G55S). The effects of these mutations were assessed here using both steady-state and presteady-state kinetic methods. While G50S and G52S reduced the apparent affinity for ATP by approximately 10-fold, substitution at Gly55 had no effect on nucleotide binding. In contrast to ATP, only mutation at position 50 inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
82
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(86 citation statements)
references
References 35 publications
(68 reference statements)
4
82
0
Order By: Relevance
“…4) which contains three highly conserved glycines that greatly control catalytic activity. [21,22] We also observed that activation of Csk through phosphopeptide binding to the SH2 domain decreases strain energies in this glycine-rich loop. [11] Likewise, in this study, activation of Csk through disulfide bond removal decreases strain in this loop.…”
Section: Discussionmentioning
confidence: 61%
“…4) which contains three highly conserved glycines that greatly control catalytic activity. [21,22] We also observed that activation of Csk through phosphopeptide binding to the SH2 domain decreases strain energies in this glycine-rich loop. [11] Likewise, in this study, activation of Csk through disulfide bond removal decreases strain in this loop.…”
Section: Discussionmentioning
confidence: 61%
“…In the crystal structure of Src (28), the side chain of Cys-277 is readily accessible, which may explain its sensitivity to oxidation. Furthermore, kinase activity appears particularly sensitive to modification to the Gly (29,30), as demonstrated for Src and Csk. All of these observations provide a mechanistic basis for the redox regulation at this residue.…”
Section: Discussionmentioning
confidence: 97%
“…The 3 Gly residues are a universally-conserved signature motif among all protein kinases, even though the intervening residues are variable. Kinetic and structural studies of both protein Ser/Thr kinase, cAMPdependent protein kinases (29), and a PTK, FPS (30), indicate that this loop is directly involved in catalysis. An examination of the amino acid sequences of all human PTKs indicates that only a small number of PTKs contain a Cys residue at the position equivalent to Cys-277 in Src (Table S1).…”
Section: Fgfr1 Responds To Redox Regulation In a Similarmentioning
confidence: 99%
“…The G-loop is one of the most flexible elements of the catalytic core and plays a key role in phosphoryl transfer. Specifically, G50 and G52 within the G-loop participate in the phosphoryl transfer reaction (16), and G55 plays a role in regulation, because it contributes to the conformational flexibility of the G-loop (17). It is notable that disease SNPs are enriched at sites involved in regulation rather than catalysis.…”
Section: N-lobementioning
confidence: 99%